2011
DOI: 10.1007/s11172-011-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-containing quinoline and quinoxaline styryl derivatives: synthesis and photophysical properties

Abstract: E) 2 Styryl substituted 6,7 difluoroquinolines and quinoxalines were synthesized by the condensation of the corresponding 2 methylbenzazines with aromatic aldehydes. Photolumines cence of the synthesized 6,7 difluoro 2 styrylbenzazines was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The quantum yield of this derivative (6%) is one log lower than with our structure (60%) . Other studies showed as for our structures that electron-withdrawing substituent induced a loss of fluorescence. …”
Section: Resultssupporting
confidence: 39%
“…The quantum yield of this derivative (6%) is one log lower than with our structure (60%) . Other studies showed as for our structures that electron-withdrawing substituent induced a loss of fluorescence. …”
Section: Resultssupporting
confidence: 39%
“…They are known antiviral agents that are a styrylquinoline inhibitors of HIV integrase [ 1 ], antifungal [ 2 ] and anticancer agents [ 3 ]. Particular attention has been paid to this class of compounds because of their electroluminescence and photochromic properties, which could permit their potential utility in optical devices or as biosensors [ 4 , 5 ]. Many reports have pointed out the feasible use of molecules such as fluorophores that could be suitable for staining intracellular components such as nucleic acids or proteins [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be observed that, as the acceptor strength increases, the emission increases. Generally, a white fluorescence is obtained by mixing three different fluorophores, emitting in the blue, green, and red, or two, one emitting in the blue and the other one in the yellow spectral range [ 19 , 34 ]. A dye emitting over a wide range of colors is thus very attractive from the applicative point of view.…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Nosov et al [ 19 ], it was shown that the lengthening in the conjugation chain in the case of change R substituent displaces the emission band to the region of a longer wavelength. In addition, it causes a transition from blue to green or yellow-orange fluorescence, regardless of the electronic nature of the group introduced.…”
Section: Introductionmentioning
confidence: 99%